Does Gotu kola supplementation improve cognitive function, inflammation, and oxidative stress more than multicomponent exercise alone? – a randomized controlled study - Phoemsapthawee J. (2023)
A randomized control trial was conducted to investigate the synergistic effects of Gotu kola supplementation and multicomponent exercise on cognitive function, inflammation, and oxidative stress in older adults with mild cognitive impairment (MCI). Sixty participants aged 74.6±7.3 years with Mini-Mental State Examination (MMSE) scores of 20.7±2.6 were randomly assigned to one of three groups: a multicomponent exercise training group (EXE, n=20), a multicomponent exercise training with Gotu kola supplementation group (EXE+GK, n=20), or a placebo-controlled group (CON, n=20). Each participant received one capsule of placebo or 500 mg twice a day of Gotu kola extract. The multicomponent exer-cise program comprised of supervised resistance, aerobic, balance and dual-task training: three 80-min sessions/week for 12 weeks. The prima-ry outcomes, such as cognitive function, inflammatory markers, and ox-idative stress, were measured before and after the 12-week interven-tion. Following the interventions, the EXE and EXE+GK had significantly higher MMSE (P<0.01), Digit Span Forward test (DSF) (P<0.01), Digit Span Backward test (P<0.01) scores, and lower Trail Making Test parts A (P<0.01) and B (P<0.01) and lower 8-iso-prostaglandin F2α (P<0.01) and tumor necrosis factor alpha (TNF-α) (P<0.01) than the CON. The change in DSF and TNF-α in the EXE+GK had a negative correlation (r=-0.504, P<0.05). In conclusion, multicomponent exercise training with or without the supplement Gotu kola improves cognitive function, inflammation, and oxidative stress in older adults with MCI. Although supplementing with Gotu kola had no additional effects on cognitive function, it may improve the effects of multicomponent exercise on ex-ecutive function by decreasing TNF-α levels.